Cross Sectional Study on The Association of Daily Spiritual Experience on Mental Well Being During COVID 19 Among The African Students In India - Sheeba Joseph (ACHSM, 2021)
Objectives: The current research focussed to explore the association of daily spiritual experience on the mental well- being of international students hails from Africa and pursuing studies in various higher education institutions in India. The research also tried to explore whether age and gender plays a significant role in the mental well- being of the respondents. Design: The study is an exploratory cross-sectional in nature. The research tool comprised of the Daily Spiritual Experience Scale (DSES) and Warwick-Edinburgh Mental Well-being Scale (WEMWBS) along with the demographic details. Post reliability and validity tests, established scales are used to study the variable in the research. The data was analysed using Smart PLS SEM 3.3.2. Setting: The respondents comprise of international students hails from Africa and pursuing various under graduate, post graduate and PhD courses from various institutions at Bhopal, Delhi, Mumbai and Rajasthan in India.  The respondents include a cohort of 102 respondents who gave consent to be part of the study during first week of July to first week of August 2021 and were selected through purposive sampling technique. Main outcome measures: The research measures the association of daily spiritual experience and mental well-being during pandemic and also the coping strategies used by the respondents. Findings: The research report shows an insignificant relation of gender to the mental well-being whereas age reported a significant association. A significant association is reported between daily spiritual experience and the mental wellbeing of the respondents amidst pandemic situation. Conclusion: Pandemic outbreaks influences the mental well-being of individuals specially when they are away from the social support system. Hence counselling services and other interventions to cater to the needs of students requires a serious deliberation at the policy level.